2018
DOI: 10.1186/s12943-018-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/CCL5 secreted by the stroma induce IL-6/PYK2 dependent chemoresistance in ovarian cancer

Abstract: BackgroundMinimal residual disease is the main issue of advanced ovarian cancer treatment. According to the literature and previous results, we hypothesized that Mesenchymal Stromal Cells (MSC) could support this minimal residual disease by protecting ovarian cancer cells (OCC) from chemotherapy. In vitro study confirmed that MSC could induce OCC chemoresistance without contact using transwell setting. Further experiments showed that this induced chemoresistance was dependent on IL-6 OCC stimulation.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…In line with our results in a chronic inflammation model, IL6 has also been reported [33] to increase epithelial tumoral cell proliferation, migration and invasion in an ovarian cancer model. Moreover, they also showed that the pro-tumoral effects can be reversed by inhibiting IL-6 both in vivo and in vitro [53]. Along the same lines of the IL-6 effect in the cancer model, IL-6 could induce up-regulation of proliferation in CRSwNP in the case of "wounded" epithelium.…”
Section: Discussionmentioning
confidence: 85%
“…In line with our results in a chronic inflammation model, IL6 has also been reported [33] to increase epithelial tumoral cell proliferation, migration and invasion in an ovarian cancer model. Moreover, they also showed that the pro-tumoral effects can be reversed by inhibiting IL-6 both in vivo and in vitro [53]. Along the same lines of the IL-6 effect in the cancer model, IL-6 could induce up-regulation of proliferation in CRSwNP in the case of "wounded" epithelium.…”
Section: Discussionmentioning
confidence: 85%
“…Microarrays for mRNA expression analysis were purchased from Affymetrix, and the analysis was conducted according to manufacturer's protocol. Briefly, RNA intensity was normalized using the Single-Channel Array Normalization (SCAN) method (Piccolo et al, 2012). Differential analysis was performed with a linear model-based approach (limma), and genes with adjusted P-value below 0.05 were considered significant (Ritchie et al, 2015).…”
Section: Microarraymentioning
confidence: 99%
“…In AML, KIT inhibition by imatinib and nilotinib was shown to be overcome in the presence of the cytokine G‐CSF (Gordon et al , ). The cytokine C‐C motif chemokine 5 (CCL5, previously known as RANTES) is physiologically a regulator of immune cell migration and was identified as constituting a distinct chemokine release cluster in AML (Bruserud et al , ) and as an important drug resistance mediator in several tumor entities: In breast, ovarian, and prostate cancer, CCL5 rendered tumor cells resistant to tamoxifen, saracatinib, cisplatin, or taxanes, respectively (Fang et al , ; Kato et al , ; Pasquier et al , ; Xiang et al , ; Yi et al , ; Zhou et al , ). In addition, CCL5 was found to contribute to tumor progression and metastasis (Azenshtein et al , ; Velasco‐Velázquez et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…[61]. As an example, the recent study highlighted that cancer-associated fibroblasts induced ovarian cancer cell chemoresistance in transmanner by secretion of CCL2/CCL5 and induction of IL-6 production [62]. Microenvironment-driven dynamic heterogeneity and phenotypic plasticity was recognized as mechanisms of therapy resistance in melanoma [35].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%